The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1016/s0889-5406(96)70070-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential scanning calorimetry (DSC) analyses of superelastic and nonsuperelastic nickel-titanium orthodontic wires

Abstract: The purpose of this study was to determine the transformation temperatures for the austenitic, martensitic, and rhombohedral (R) structure phases in representative as-received commercial nitinol (NiTi) orthodontic wire alloys, to reconcile discrepancies among recent publications. Specimens were examined by differential scanning calorimetry (DSC) over a temperature range from approximately -170 degrees C to 100 degrees C, with a scanning rate of 10 degrees C per minute. Two different pathways, with the intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
66
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(81 citation statements)
references
References 13 publications
(6 reference statements)
11
66
1
3
Order By: Relevance
“…As known, transformations temperatures can be determined by differential scanning calorimetry [221,222], dilatometry [223] or electrical resistivity [224,225]. However, transformation temperatures of the thermal affected regions in NiTi welds have been mostly determined by differential scanning calorimetry, despite their small dimensions.…”
Section: Phase Transformation Temperaturesmentioning
confidence: 99%
“…As known, transformations temperatures can be determined by differential scanning calorimetry [221,222], dilatometry [223] or electrical resistivity [224,225]. However, transformation temperatures of the thermal affected regions in NiTi welds have been mostly determined by differential scanning calorimetry, despite their small dimensions.…”
Section: Phase Transformation Temperaturesmentioning
confidence: 99%
“…Subsequently, the specimen was cooled from 100 back to 70 to obtain the cooling DSC curve. Linear heating or cooling rate was a standard 10 per minute 19) for each analysis. The DSC cell was purged with dry nitrogen at a rate of 50 cm Temperature calibration of the DSC apparatus was performed with deionized water and indium.…”
Section: Dsc Analysis Dsc Analysesmentioning
confidence: 99%
“…In addition, recent studies 17,18) published in endodontic literature have indicated that the structure of NiTi rotary instruments can be conveniently investigated by differential scanning calorimetry (DSC). With this analytical technique, the difference in thermal power supplied to a test specimen and an inert control specimen heated at the same rate is measured very accurately 19,20) .…”
Section: Introductionmentioning
confidence: 99%
“…Conventional analytical techniques for determining the phase transformation characteristics of NiTi shape memory alloys are differential scanning calorimetry (DSC) [7,8] and X-ray diffraction [9,10] using conventional lab sources. However, these techniques are not suited to provide the spatial resolution required for an in-depth understanding of the microstructural changes occurring along both the heat affected and fusion zones due to the laser welding procedure.…”
Section: Introductionmentioning
confidence: 99%